Optimizing Laundry Wastewater Treatment: A Hybrid Approach Using Poly-Aluminum Chloride Coagulation and Activated Carbon Adsorption - Sugito, Sugito; Ambima, Aliffia Rica; Al Kholif, Muhammad; Fitria, Firda Lutfiatul (Institut Teknologi Sepuluh Nopember, 2025)
Laundry wastewater contains high levels of Chemical Oxygen Demand (COD) and phosphate (PO₄), contributing to water pollution and eutrophication. This study investigates an integrated treatment approach using poly-aluminum chloride (PAC) coagulation and activated carbon adsorption to improve wastewater treatment efficiency. The research aims to determine the optimal PAC dosage (10% and 15%) and stirring time (0, 5, 15, 30, and 45 minutes) for maximizing COD and PO₄ removal. A batch reactor system was used to conduct the treatment process, and the analysis followed the Indonesian National Standard (SNI) methods. The results demonstrated that the highest removal efficiencies were achieved with a 15% PAC dosage and a stirring time of 45 minutes. Under these conditions, COD levels were reduced from 2189.62 mg/L to 143.47 mg/L, achieving a 93% reduction. Similarly, PO₄ levels decreased from 94.33 mg/L to 5.18 mg/L, corresponding to a 96% removal rate. These findings indicate that the combination of PAC coagulation and activated carbon adsorption is a highly effective treatment method for reducing pollution in laundry wastewater. This hybrid approach meets environmental discharge standards and presents a sustainable solution for large-scale wastewater treatment applications.